2019
DOI: 10.1182/bloodadvances.2019000545
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte and red blood cell deformation triggers specific phosphorylation events

Abstract: The capacity to undergo substantial deformation is a defining characteristic of the red blood cell (RBC), facilitating transit through the splenic interendothelial slits and microvasculature. Establishment of this remarkable property occurs during a process of reticulocyte maturation that begins with egress through micron-wide pores in the bone marrow and is completed within the circulation. The requirement to undertake repeated cycles of deformation necessitates that both reticulocytes and erythrocytes regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Upregulation of band-3 and interacting partners in SCD RBC (compared to controls) was also confirmed in earlier studies linking phosphorylation of these proteins with oxidative stress in humans 31,33 . Because we see a higher relative abundance of both PTMs in SCD patients, our proteomic data and orthogonal studies suggest that both PTMs of this band-3 interaction network are associated with MP formation.…”
Section: Discussionsupporting
confidence: 79%
“…Upregulation of band-3 and interacting partners in SCD RBC (compared to controls) was also confirmed in earlier studies linking phosphorylation of these proteins with oxidative stress in humans 31,33 . Because we see a higher relative abundance of both PTMs in SCD patients, our proteomic data and orthogonal studies suggest that both PTMs of this band-3 interaction network are associated with MP formation.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, reticulocytes have a highly active protein kinase [ 114 ] and more phosphorylated peptides are derived from reticulocytes when passed through a micro-filtration system compared to RBCs [ 115 ]. Phosphorylation regulates cytoskeletal and membrane interactions which contribute to membrane stability.…”
Section: Mature Red Blood Cell Versus Immature Red Blood Cell Membranementioning
confidence: 99%
“…Indeed, we have also shown that native reticulocytes, when incubated in either plasma or media at 37°C for ten days, reduce their levels of RNA and TfR and develop an increased ratio of R2:R1 reticulocytes (data not shown). Cultured reticulocytes can be induced to begin the maturation process when put under shear stress ( Moura et al, 2019 ) and appear to mature fully in the circulation of a mouse model ( Kupzig et al, 2017 ) but completing the maturation process in vitro has yet to be achieved. Proteomic analysis comparing native reticulocytes to cultured reticulocytes shows their proteomic profile to be very similar ( Moura et al, 2018 ) but there must be an essential factor missing from the cRBCs (perhaps a plasma protein or the lack of macrophages) that restricts their development in vitro .…”
Section: Discussionmentioning
confidence: 99%